Rating Evaluation of Ecological Effects from the Operation of Agricultural Enterprises - Т. V. Kobylynska (Статистика України, 2017)
Problems related with ecological effects of the operation of agricultural enterprises are analyzed. Statistical rating evaluation of regions from the perspective of ecological effects is made.